INCREASING ECONOMIC LITERACY ONLINE ROLE OF SERVICES - Umurzak, Chorshanbayev; Lobar, Muratjanova (Journal of Higher Education and Academic Advancement, 2024)
Economic experts of a number of international financial organizations are conducting research in various directions on various methodological approaches to assessing the level of financial literacy of the population. These studies are focused on evaluating the ability of households, families and individuals (the person himself) to manage their financial resources and their effective decisions by assessing the level of financial literacy of the population. In addition, the influence of the level of financial literacy of the population on the standard of living of the population is also evaluated. In this case, the monetary characteristics of households, families or individuals are formed through monetary indicators.